Protection of Swimming-Induced Oxidative Stress in Some Vital Organs by the Treatment of Composite Extract of Withania Somnifera, Ocimum Sanctum and Zingiber Officinalis in Male Rat - Misra, Debanka Sekhar (African Networks on Ethnomedicines, 2009)
Composite methanolic extract of roots of Withania somnifera, leaves of Ocimum sanctum, and rhizomes of Zingiber officinalis was administered by gavage at the dose of 40 mg 100 g(−1) body weight day(−1) to rat orally for 15 days prior to experimentation followed by co-administration of above extract at the same dose for 28 days of swimming to find out the remedial effect of this extract on exhaustive physical exercise-induced oxidative damage. Swimming resulted significant diminution (p<0.05) in the activities of catalase and superoxide dismutase along with elevation (p<0.05) in the levels of thiobarbituric acid reactive substances and conjugated dienes in cardiac, skeletal, hepatic tissues, cerebrum and cerebellum in respect to control. The levels of all these parameters were resettled significantly (p<0.05) towards the extract pretreated cum co-treated swimming group. The antioxidative potency of this composite extract was compared with standard non-enzymatic antioxidant (vitamin-E) in forced swimming state. The above extract has no general toxic effect as reflected here from the study of transaminase activities in liver and kidney. Results lead to conclude that the composite extract of above three plant parts has a therapeutic protective effect on forced swimming-induced oxidative stress in vital organs.